A miniaturized multi-beam wideband high gain-5g antenna based on a novel design of compact 4x4 Butler matrix - Sadiq, Mohammed; Sulaiman, Nasri; Mohd Isa, Maryam; Hamidon, Mohd Nizar; Talib, Muntadher (UIKTEN - Association for Information Communication Technology Education and Science, 2024)
This research focuses on developing a uniquely miniaturized 4×4 Butler Matrix Network integrated with a 1×4 linear array antenna, generating four beams with exceptional isolation and transmission coefficients. Extensive analyses evaluate the antenna's radiation characteristics, including gain, directivity, and beam-forming capabilities. Innovative design techniques achieve significant Butler matrix miniaturization without compromising performance, resulting in a compact final design measuring 23mm × 20.5mm. The integrated multi-beam antenna array demonstrates favorable outcomes, ensuring impedance matching at 50Ω, high gain, and four beams directed at angles of ±8º and ±33º. These results highlight the design's superiority over traditional counterparts, with gains of up to 11 dB. Detailed radiation patterns for all ports are presented. The paper also provides insights into the manufacturing process, materials used, and challenges faced. The results conclusively confirm the system's compliance with performance criteria, effectively operating within the 28 GHz frequency band. This research significantly contributes to downsizing antenna systems, facilitating more compact and efficient communication devices in the future. © 2024 Mohammed Sadiq et al; published by UIKTEN. This work is licensed under the Creative Commons Attribution-NonCommercial-NoDerivs 4.0 License. The article is published with Open Access at https://www.temjournal.com/